Tracking Multimodal Literacy in Schools: a Case Study - Komninos, Nickolas (Revija za elementarno izobraževanje, 2023)
This paper presents tools which can be used to measure multimodal literacy and metasemiotic awareness in students. The results are interesting within the context of multiliteracy development both in terms of the individual student over time or in comparison to other students within a specific course, as well as when comparing data from larger cohorts for example differences in level or orientation of education, age, regional, territorial, national and so on to see patterns or strengths and weaknesses in multimodal literacy within a wider perspective.
Keywords: multimodality, literacy, multiliteracy, metaseiotic awareness